Multidrug-Resistant Tuberculosis: Treatment and Outcomes of 93 Patients. Issue 2 (2015) - Brode, Sarah K; Varadi, Robert; McNamee, Jane; Malek, Nina; Stewart, Sharon; Jamieson, Frances B; Avendano, Monica
Abstract : BACKGROUND: Tuberculosis (TB) remains a leading cause of death worldwide and the emergence of multidrug-resistant TB (MDR TB) poses a threat to its control. There is scanty evidence regarding optimal management of MDR TB. The majority of Canadian cases of MDR TB are diagnosed in Ontario; most are managed by the Tuberculosis Service at West Park Healthcare Centre in Toronto. The authors reviewed 93 cases of MDR TB admitted from January 1, 2000 to December 31, 2011. RESULTS: Eighty-nine patients were foreign born. Fifty-six percent had a previous diagnosis of TB and most (70%) had only pulmonary involvement. Symptoms included productive cough, weight loss, fever and malaise. The average length of inpatient stay was 126 days. All patients had a peripherally inserted central catheter for the intensive treatment phase because medications were given intravenously. Treatment lasted for 24 months after bacteriologic conversion, and included a mean (± SD) of 5±1 drugs. A successful outcome at the end of treatment was observed in 84% of patients. Bacteriological conversion was achieved in 98% of patients with initial positive sputum cultures; conversion occurred by four months in 91%. CONCLUSIONS: MDR TB can be controlled with the available anti-TB drugs.